A Study on Automatic Speech Recognition Systems - Ibrahim, Habib; Varol, Asaf (Institute of Electrical and Electronics Engineers Inc., 2020)
Speech recognition is a technique that enables machines to automatically identify the human voice through speech signals. In other words, it helps create a communication link between machines and humans. Speech recognition uses an acoustic and modeling algorithm to execute its task. It allows interaction between computer interfaces and a natural human voice. Speech recognition is one of the current topics of discussion in the twenty-first century. The advent of technological gadgets in modern society has become rampant through vigorous efforts made by scientists in realizing their aim of developing an algorithm that will allow machines to interact with human beings. It is obvious that this situation previously thought of as fiction, has been achieved. Hence, there are several applications that enhance speech recognition. This paper aims to study some models of the speech recognition system, its classification of speech, its significance, and its application. © 2020 IEEE.
8th International Symposium on Digital Forensics and Security, ISDFS 2020 -- 1 June 2020 through 2 June 2020 -- Beirut -- 161222
Keywords: algorithm; speech recognition; speed signals; techniques